World Health Organization Recommendation for Using Uterine Balloon Tamponade to Treat Postpartum Hemorrhage. Issue 3 (March 2022) - Weeks, Andrew D.; Akinola, Oluwarotimi Ireti; Amorim, Melania; Carvalho, Brendan; Deneux-Tharaux, Catherine; Liabsuetrakul, Tippawan; Meremikwu, Martin; Miller, Suellen; Nabhan, Ashraf; Nagai, Mari; Wahabi, Hayfaa; Walker, Dilys
Abstract : The World Health Organization (WHO) recently published a new recommendation on the use of the uterine balloon tamponade for the treatment of postpartum hemorrhage. The recommendation that uterine balloon tamponade should be used only where there is already access to other postpartum hemorrhage treatments (including immediate recourse to surgery) has proved controversial. It is especially problematic for those working in low-level health care facilities in under-resourced settings, where there are already programs that have introduced low-cost uterine balloon tamponade devices for use, even in settings where recourse to surgical interventions is not possible. However, there are now two separate randomized trials that both unexpectedly show unfavorable outcomes in these settings when a condom catheter uterine balloon tamponade device was introduced. Considering the balance of potential benefits and these safety concerns, the WHO postpartum hemorrhage guideline panel therefore recommends that uterine balloon tamponade should be used only in contexts where other supportive postpartum hemorrhage interventions are available if needed. Abstract : The World Health Organization recommends that balloon tamponade should be used only where other supportive interventions are available if needed.